WEBSITE DESIGN IN APPLIED MANAGEMENT INSTITUTIONS TRUSTCO USING MACROMEDIA FLASH MX - Sugeng Prasetyo Nugroho; Yudi Irawan Chandra, SKom, MMSI Yudi Irawan Chandra, SKom, MMSI (Jurnal Sistem Informasi, 2005)
In scientific writing, the author makes LMT TRUSTCO website using MacromediaFlash MX. This program created with the aim of helping the user get informationabout TRUSTCO. This website uses elements of images, text, sound, and animationinto a website that is expected to form easily used by anybody and made as attractiveas possible with the music that accompanies this website. In the discussion of thisissue to be discussed is about how to manufacture from start to determine thestructure of navigation, making navigation map, making the design interface, theformation of elements, the combination of elements, ActionScript programming so itcan run.With the push of a button from the menu options the user will immediately getinformation quickly about LMT TRUSTCO. This program can only run on Windowsplatform.